Advanced topics on cellular self-organizing nets and chaotic nonlinear dynamics to model and control complex systems - Caponetto, Riccardo; Fortuna, Luigi; Frasca, Mattia (Nonlinear Science, Series A: Monographs and Treatises, 2008)
This book focuses on the research topics investigated during the three-year research project funded by the Italian Ministero dell'Istruzione, dell'Università e della Ricerca (MIUR: Ministry of Education, University and Research) under the FIRB project RBNE01CW3M. With the aim of introducing newer perspectives of the research on complexity, the final results of the project are presented after a general introduction to the subject. The book is intended to provide researchers, PhD students, and people involved in research projects in companies with the basic fundamentals of complex systems and the advanced project results recently obtained.